Legal protection of scenic arts and their creative elements - Larrea, Karina (2019)
In Ecuador, the current regulations on copyright protect the theater scripts, dramatic or theatrical works, choreographies and pantomimes. On the other hand, neighboring rights protect the performances of the artist and performers of a previously existing work. However, those of us who have ever attended as spectators to some theatrical work, opera, circus show, ballet, etc. know that the scenic work can be seen as a whole, in other words, as a single spectacle, but also as a set of elements with a lesser or greater degree of creativity that deserve sufficient protection. National, community and international legal norms provide different forms and levels of protection to holders of copyright and related rights if their works (in the case of authors) or their actions and interpretations (in the case of artists or performers) are original or reach a high level of creativity. The present essay intends to identify the applicable legislation to the scenic arts and their creative elements in Ecuador as well as the scope of their protection.